Effect of inorganic phosphate on migration and osteogenic differentiation of bone marrow mesenchymal stem cells - Lin, Hengzhang (BMC Dev Biol, 2021)
BACKGROUND: Phosphate is the major ingredient of bone tissue, and is also an important component of commercial bone substitute materials, bone scaffolds, and implant surface coatings. With the dissolution of the bone substitute materials and the degradation by cells, local ion concentrations will change and affect bone tissue reconstruction. Bone marrow -derived mesenchymal stem cells (BM-MSCs) are main autologous cells to repair injured bone. When bone injure occurs, BM-MSCs migrate to the damaged area, differentiate into osteoblasts, and secrete bioactive factors to promote bone tissue repaired. This study aimed to investigate the effect of inorganic phosphate (Pi) at a series of concentration on migration and osteogenic differentiation of human bone marrow -derived mesenchymal stem cells(hBM-MSCs). METHODS: The culture of hBM-MSCs in mediums with different concentration of Pi from 2 mM to 10 mM were performed. HBM-MSCs migration were examined with transwell assays. HBM-MSCs proliferation were evaluated by cell counting kit-8 colorimetric method. Osteogenic genes expression were analyzed by real-time reverse transcriptase polymerase chain reaction. Mineralized nodules formation were demonstrated by Alizarin red staining. RESULT: 4–10 mM Pi could effectively promote the migration of hBM-MSCs at 12 h and 18 h. There was no significant difference in the migration number of hBM-MSCs in Pi culture mediums at a concentration of 6, 8, and10mM. 2–10 mM Pi could promote the proliferation of hBM-MSCs to varying degrees in the observation period, while 4–10 mM Pi could promote the osteogenic differentiation and mineralization of hBM-MSCs. CONCLUSION: The findings in our study showed 4-10 mM Pi could promote the migration, osteogenic differentiation, and mineralization of hBM-MSCs. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12861-020-00229-x.